Survival analysis on adult extremity soft tissue sarcoma : a single institution study of 10 years duration - Yusof, Wan Yuhana W Md (2017)
Soft tissue sarcoma is one of the commonest orthopaedic related malignancy. Approximately 80% of sarcoma arises from soft tissue and 20 % from bone⁸ ³. However, from the general point of view, soft tissue sarcoma is one of the rarest malignancies with incidence reported was less than 1%. Its classification is based on the direction of the differentiation of the soft tissue either collagen (fibrous tissue), fat or cartilage for instance. Several demographic factors and a few other possible prognostic factors have been demonstrated previously that may influence the patients’ survival. This study involved 128 patients for 10 years duration (1st January 2001- 31st January 2010) from one of the tertiary center for orthopaedic oncology in the country. Besides demographic studies, the prognostic clinical characteristics were assessed for differences in overall survival by using Kaplan Meier method as well as Cox proportional hazard regression. From this study, it was found the overall median survival time was 10 years with 5- year overall survival of 58%. No demographic results were statistically significant in affecting the overall survival (age, sex, sites of tumor, and subtypes, p-value >0.05). Treatments of soft tissue sarcoma for example limb salvage or amputation surgery, pre- and post- operative chemotherapy and radiotherapy, as well as outcome of the tumor which was second malignancy were all not statistically significant as well (p- value >0.05). Pulmonary and distant (non-pulmonary) metastasis, and local recurrence were the prognostic factors that significantly affect the overall survival (p <0.001). Nevertheless, after a multivariate analysis, only pulmonary (CI:3.08, p <0.001) and distant (non-pulmonary) (CI:2.30, p <0.004) metastasis were significantly associated with survival.